2020
DOI: 10.1038/s41598-019-57208-x
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Combination of Tensile ductility and strength due to nanotwinning and a biamodal structure in cryorolled austenitic stainless steel

Abstract: grains. The very short annealing periods prevented grain growth while still retaining good amount of dislocation density (Fig. 7). Similar observations were also reported in case of TWIP steels by Tewari et al. 28. conclusions The effect of Cryogenic and room temperature rolling on the strength and ductility of UNS S31000 austenitic stainless steel was investigated for 50% and 75% thickness reductions. A five-fold enhancement in the strength is observed under Cryorolled conditions while room temperature rollin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Cryorolling is considered to be the prominent processing method to develop high strength materials. Even though considerable work is available on mechanical properties of cryorolled materials, mainly light alloys, titanium, and steels [27][28][29][30][31][32][33][34][35][36][37][38]. Cryorolling can improve strength and ductility therefore opening up further opportunities to applications in even more strength critical applications.…”
Section: Rolling Directionmentioning
confidence: 99%
“…Cryorolling is considered to be the prominent processing method to develop high strength materials. Even though considerable work is available on mechanical properties of cryorolled materials, mainly light alloys, titanium, and steels [27][28][29][30][31][32][33][34][35][36][37][38]. Cryorolling can improve strength and ductility therefore opening up further opportunities to applications in even more strength critical applications.…”
Section: Rolling Directionmentioning
confidence: 99%
“…It has been reported that dislocation slip is the main deformation mode when copper is severely deformed at room temperature [26,27]. However, the deformation of SMAT at cryogenic temperatures reduces dynamic recovery and recrystallization, and the deformation mechanism of grain refinement changes from dislocation to twin [28], which promotes the formation of twins. Therefore, a higher density of twins can be obtained through processing at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%